A comprehensive model on the transport phenomena during gas metal arc welding process. (1st January 2004) - Zhu, F.L.; Tsai, H.L.; Marin, S.P.; Wang, P.C.
A comprehensive mathematical model and the associated numerical technique have been developed to simulate the coupled, interactive transport phenomena between the electrode (droplets), the arc plasma, and the workpiece (weld pool) during a stationary axisymmetric gas metal arc welding process. The simulation involves arc plasma generation, electrode melting, droplet formation, detachment, transfer, and impingement onto the workpiece, and weld pool dynamics. During transfer from the tip of the electrode to the workpiece, the droplet subjects to gravity, electromagnetic force, surface tension, and arc plasma drag force. Transient temperature and velocity distributions of the arc plasma, shapes of the electrode, droplet, and weld pool, and heat transfer and fluid flow in the weld pool are all calculated in a single, unified model. The predicted solidified weld bead shape compares favourably with the experimental result.